Comparing SMILES and SELFIES Tokenization for Enhanced Chemical Language Modeling - Leon, Miguelangel (2024)
Leon, M., Perezhohin, Y., Peres, F., Popovic, A., & Castelli, M. (2024). Comparing SMILES and SELFIES Tokenization for Enhanced Chemical Language Modeling. Scientific Reports, 14, Article 25016. https://doi.org/10.1038/s41598-024-76440-8 --- This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project - UIDB/04152/2020 (DOI: 10.54499/UIDB/04152/2020) - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS). Aleš Popovič was supported by the Slovenian Research and Innovation Agency (ARIS) under research core funding P2-0442